2016
DOI: 10.20507/alternative.2016.12.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Daughters of the Drum: Decolonizing health and wellness with Native American women

Abstract: In many pre-colonial tribal communities, Native American women held significant positions as keepers and teachers of health and wellness practices. Today, however, Native American women's status is often relegated to the margins in colonial society, as they are disproportionately affected by health disparities resulting from legacies of historical trauma. This study explores the decolonization of the health and wellness of Native American women in the United States Pacific Northwest. Through a culturally cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Our study provides an empirical example of how such a deficit discourse framed a detrimental Indigenous affairs policy in Australia. Our findings also accord with calls for public policy affecting Indigenous Peoples to be based on Indigenous knowledges rather than colonial knowledges (Brown, 2016;Came et al, 2019;McLeigh, 2010).…”
Section: International Implicationssupporting
confidence: 84%
“…Our study provides an empirical example of how such a deficit discourse framed a detrimental Indigenous affairs policy in Australia. Our findings also accord with calls for public policy affecting Indigenous Peoples to be based on Indigenous knowledges rather than colonial knowledges (Brown, 2016;Came et al, 2019;McLeigh, 2010).…”
Section: International Implicationssupporting
confidence: 84%
“…Other authors may have identified as Indigenous but not noted it within the article text. Materials and methods (meaningful data collection, research) As data collection instruments, studies employed digital cameras ( n = 22), disposable cameras ( n = 12), or cameras of an unspecified type ( n = 10) for photo‐taking. Other methods included smartphones (Brown, 2016; Holliday et al, 2018; Spiegel et al, 2020), a GPS with camera capabilities (Isogai et al, 2015), GoPros (Ahmed et al, 2022, 2023), or a tablet shared between all participants (Kahn‐John et al, 2020). Six studies did not specify the photo‐taking method used.Nine studies combined other data collection methods with photo‐taking.…”
Section: Resultsmentioning
confidence: 99%
“…One study collected photo and video data using researcher‐supplied cameras and video recorders (Lines et al, 2019). In Brown's (2016) participant‐led study, photos were taken with smartphones or created using Adobe Photoshop.Most studies ( n = 50) commenced data collection through sessions with participants to discuss the study purpose, photography techniques and ethics, and to distribute cameras. The duration of these initial meetings or workshops varied from a few hours to a few days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals under 18 years of age will not be included in the study. Due to the inclusive and flexible research philosophy, no individuals are specifically excluded because that will be for First Nations community members to advise according to their local protocols; however, this is a gender-specific Indigenist approach and the lead researcher is a female non-First Nations Australian [54,55].…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%